Human-Effective Computability. Issue 1 (24th June 2018) - Antonutti Marfori, Marianna; Horsten, Leon
Abstract: We analyse Kreisel's notion of human-effective computability . Like Kreisel, we relate this notion to a concept of informal provability, but we disagree with Kreisel about the precise way in which this is best done. The resulting two different ways of analysing human-effective computability give rise to two different variants of Church's thesis. These are both investigated by relating them to transfinite progressions of formal theories in the sense of Feferman.